Avaliação da coastcross-1 inoculada com Azospirillum brasilense - Aguirre, Priscila Flôres (2017)
Researches with the use of inoculants containing bacteria that promote plant growth have been increasing over the years, due to concerns about pollution and high costs of fertilizers. Therefore the objective of this research was to evaluate the forage yield, nutritive value, biological nitrogen fixation (BNF) and the N recovery of Coastcross-1 pastures inoculated with Azospirillum brasilense subjected to cut. The experimental design was randomized blocks with three replications, in a factorial scheme. The factors were the inoculation (without inoculation, inoculated just in the implantation and reinoculated in the second year), levels of nitrogen (0, 100 and 200 kg of N/ha/year) and periods of the years where cuts were made. Forage yield, daily accumulation rate, forage mass, botanical and structural pasture composition, crude protein content, in situ digestibility of organic matter and total digestible nutrients of Coastcross-1 were evaluated during two years. Forage yield without nitrogen fertilizer use in pastures was in the first year 9.1, 11.7 and 11.7 t of DM/ha, and in the second year 8.6, 11.2 and 11.5 t of DM/ha, to inoculation factor, respectively. The average Coastcross-1 contribution in pastures without nitrogen fertilization was 47.9, 58.5 and 62.7%, respectively to the inoculation. There was reduction in Coastcross-1 crude protein content when pasture fertilized with 200 kg of N/ha/year was inoculated. The forage yield and Coastcross-1 contribution rises with the inoculation without nitrogen fertilizers use; and reinoculation is not necessary. To evaluate BNF and the N recovery two treatments were considered for each variable. Evaluations were carried out during one year. To estimate the BNF the treatments were: Coastcross-1 inoculated and Coastcross-1 uninoculated, both without nitrogen fertilization. The biologically fixed nitrogen was 53.8 and 23.0 kg/ha/year for Coastcross-1 inoculated and uninoculated, respectively. In Coastcross-1 without nitrogen fertilization, inoculation elevates the BNF. To estimate the N recovery the treatments were: Coastcross-1 inoculated and Coastcross-1 uninoculated, both fertilized with 100 kg of N/ ha/year. Isotopic recovery of N was 16.5 and 13.7 kg/ha/year for Coastcross-1 inoculated and uninoculated, respectively. Inoculation increases recovery of N in Coastcross-1. The forage yield increase when don’t use nitrogen fertilizers with the inoculation is related to the increase of biological nitrogen fixation.